Conjunction, cumulation and respectively readings - CHAVES, RUI P. (Journal of linguistics, 2012)
So-called respectively readings have posed serious challenges for theories of syntax and semantics. Sentences like George and Martha respectively denounced and were denounced by the governor (McCawley 1998) show that although the conjoined verbal expressions share the same syntactic subject, they do not predicate that subject in the same way; George (not Martha) denounced the governor, and Martha (but not George) was denounced by the governor. Postal (1998: 160-163) and Gawron & Kehler (2004: 193-194) show that this phenomenon poses problems for contemporary theories of grammar and argue that it is particularly acute for theories where subcategorization and predication are linked via unification. As these authors note, the problem is even more severe in respectively readings involving filler-gap constructions. In this paper I argue that the severity of these problems has been overstated and that the data do not entail any special dissociation between predication, subcategorization, or extraction. In this paper I propose an account which is fully compatible with unification-based theories of grammar. Gawron & Kehler (2004) propose an account of respectively phenomena which covers a remarkably wide range of cases. That approach relies on a Respf operator, which it stipulated to be optionally overt. However, I argue that this analysis is problematic because there are significant semantic differences between respectively readings with and without an overt realization of respectively '. Rather, the data suggest that respectively readings may be special cases of more general phenomena which happen to create interpretations that are compatible with the semantics of the adverb respectively. This explains why respectively readings can arise without the adverb, and does not require us to posit a disconnect between predication and subcategorization. In fact, a sentence with a respectively reading will not differ in syntactic or semantic structure from sentences without such a reading.